The problems of proving the status of the possessor according to the possession certificate - LEMBOUB, Rania (Journal of Human Sciences, 2025)
Possession is a factual condition that is difficult to prove, especially since written evidence is not required for its proof. Therefore, the possession certificate was introduced as a means to accelerate the process of land organization. It serves as a legal possession document on which the holder relies to prove their status and to use possession as a means to acquire ownership. The certificate produces its legal effect and does not require other evidence to prove its validity, placing the holder in a privileged legal position. However, the certificate only confirms the possession of its holder at the date of its issuance. Possession may be interrupted, or the certificate may be revoked, especially since it remains subject to cancellation without a specific time limit. This raises issues concerning the legal effects that the possession certificate may have established, such as the possibility of obtaining a building permit or arranging a mortgage. Thus, legislative intervention is required to address the imbalances in the real estate system.